Šeškauskienė, Inesa, 2013. Ways with Words: Insights into the English Lexicon and Some Cross-Linguistic Aspects of Study - Ostanina-Olszewska, Julia (Respectus Philologicus, 2014)
ŠEŠKAUSKIENĖ, Inesa, 2013. Ways with Words: Insights into the English Lexicon and Some Cross-Linguistic Aspects of Study. Vilnius: Vilnius University Publishing House. 464 p. ISBN 978-609-459-199-0.
Keywords: none